Multifunctional cationic nanosystems for nucleic acid therapy of thoracic aortic dissection - Chen Xu (Nature Portfolio, 2019)
Thoracic aortic dissection has a high fatality rate and no effective treatment. Here, the authors develop cationic nanoparticles for the delivery of miR-145 and show that they stabilize vascular structures and prevent further deterioration of the aorta in mouse models of the disease.